Severity-dependent IgG epitope profiling in COVID-19 reveals differential recognition of pathogen-derived antigens - do Nascimento, Lais Alves; Machado, NicolleRakanidis; Borges, João Vitor da Silva; Fagundes, Beatriz Oliveira; Bergamasco, Isabella Siuffi; Sgnotto, Fabio da Ressureição; Bachi, André Luis Lacerda; Sato, Maria Notomi; Victor, Jefferson Russo (Frontiers in Immunology, 2025)
BackgroundThe contribution of antibody-mediated responses to COVID - 19 outcomes remains unclear, particularly regarding cross-reactivity with unrelated pathogens. While co-infections are known to influence disease progression, the broader landscape of IgG reactivity during SARS-CoV-2 infection has not been systematically explored.MethodsWe employed a high-density peptide microarray containing 4,344 linear epitopes from 37 viruses, 27 bacteria, 17 parasites, and 8 fungi to characterize serum IgG repertoires from individuals with moderate (n = 39) or severe (n = 40) COVID - 19. Controls included pre-pandemic healthy donors and a pooled intravenous immunoglobulin (IVIg) formulation. Data analysis included intensity ranking, epitope mapping, and comparative analysis of mean signal intensities for each epitope between the COVID-Mod and COVID-Sev groups.ResultsCOVID - 19 patients showed widespread IgG reactivity against diverse pathogens, with patterns differing by disease severity. Severe cases displayed broader and more intense reactivity, notably against hepatitis C virus (HCV), SARS-CoV-1, influenza A, Mycobacterium tuberculosis, and Plasmodium falciparum. Moderate cases showed preferential recognition of epitopes from HTLV-I, Neisseria meningitidis, and Trypanosoma cruzi. These findings suggest that SARS-CoV-2 infection modulates pre-existing humoral memory, possibly through epitope spreading or immune reprogramming.ConclusionsSARS-CoV-2 infection reshapes the IgG epitope repertoire in a severity-dependent manner, extending to antigens from unrelated pathogens. This phenomenon may reflect underlying immune dysregulation or idiotype-driven interactions. Comprehensive profiling of pathogen-related IgG responses may reveal potential biomarkers of disease severity. This phenomenon may inform future investigations aimed at improving personalized management strategies for co-infected or immunocompromised patients.